Targeted next‐generation sequencing of 22 mismatch repair genes identifies Lynch syndrome families. (25th January 2016) - Talseth‐Palmer, Bente A.; Bauer, Denis C.; Sjursen, Wenche; Evans, Tiffany J.; McPhillips, Mary; Proietto, Anthony; Otton, Geoffrey; Spigelman, Allan D.; Scott, Rodney J.
Abstract: Causative germline mutations in mismatch repair (MMR) genes can only be identified in 50% of families with a clinical diagnosis of the inherited colorectal cancer (CRC) syndrome hereditary nonpolyposis colorectal cancer (HNPCC)/Lynch syndrome (LS). Identification of these patients are critical as they are at substantially increased risk of developing multiple primary tumors, mainly colorectal and endometrial cancer (EC), occurring at a young age. This demonstrates the need to develop new and/or more thorough mutation detection approaches. Next‐generation sequencing (NGS) was used to screen 22 genes involved in the DNA MMR pathway in constitutional DNA from 14 HNPCC and 12 sporadic EC patients, plus 2 positive controls. Several softwares were used for analysis and functional annotation. We identified 5 exonic indel variants, 42 exonic nonsynonymous single‐nucleotide variants (SNVs) and 1 intronic variant of significance. Three of these variants were class 5 (pathogenic) or class 4 (likely pathogenic), 5 were class 3 (uncertain clinical relevance) and 40 were classified as variants of unknown clinical significance. In conclusion, we have identified two LS families from the sporadic EC patients, one without a family history of cancer, supporting the notion for universal MMR screening of EC patients. In addition, we have detected three novel class 3 variants in EC cases. We have, in addition discovered a polygenic interaction which is the most likely cause of cancer development in a HNPCC patient that could explain previous inconsistent results reported on an intronic EXO1 variant. Abstract : This study provides evidence that mutations in mismatch repair screening is highly relevant to endometrial cancer diagnostics and that polygenic interactions may be causative in hereditary nonpolyposis colorectal cancer. There is potential for rapid uptake of these testing strategies to the clinic through only small modifications to target regions of molecular tests, or expansion of the patient referral criteria.